Pemanfaatan Metaverse Di Bidang Pendidikan - Iswanto; Putri, Novianti Indah; Widhiantoro, Dandun; Munawar, Zen; Komalasari, Rita (LPPM POLITEKNIK LP3I BANDUNG, 2022)
The impact of Covid-19, the increasing number of new technologies being applied in education, as well as increasing interest in the metaverse. Closely related to this virtual environment is life in the field of education. This study aims to explain the type of metaverse, the potential and limitations of its educational application. The four metaverse categories emphasize different functions, types, or sets of Metaverse technologies. There are four spectrums of technologies and applications in the metaverse, namely augmentation, simulation, intimate technology, and external technology. The use of augmented reality in health is in the form of virtual clothes so that you can examine parts as human anatomy laboratory simulation. Spinal surgery that applies virtual technology. Utilization in the learning environment is through new forms of social communication space, freer settings for creation and sharing, and additional virtual experiences. The limitations of the metaverse are weaker social relations, and users of the metaverse who do not have an identity, and the abuse of simulation as a representative of student identity in the everyday world. Prediction of changes in daily life patterns as a negative impact of the metaverse. However, the unlimited opportunity to be a form of communication in social life is the hallmark of the metaverse. It is hoped that in the future it is recommended to use the metaverse in education, namely the teacher must conduct a careful analysis beforehand so that students can gain knowledge in the metaverse, the teacher must prepare class designs for students so that they can solve problems and carry out activities cooperatively, adaptively and creatively. Instructional designers and educators need to understand well the type of category and class metaverse.